The Modulating Role of Sex and Anabolic-Androgenic Steroid Hormones in Cannabinoid Sensitivity - Struik, Dicky; Sanna, Fabrizio; Fattore, Liana (Frontiers in Behavioral Neuroscience, 2018)
Cannabis is the most commonly used illicit drug worldwide. Although its use is associated with multiple adverse health effects, including the risk of developing addiction, recreational and medical cannabis use is being increasing legalized. In addition, use of synthetic cannabinoid drugs is gaining considerable popularity and is associated with mass poisonings and occasional deaths. Delineating factors involved in cannabis use and addiction therefore becomes increasingly important. Similarly to other drugs of abuse, the prevalence of cannabis use and addiction differs remarkably between males and females, suggesting that sex plays a role in regulating cannabinoid sensitivity. Although it remains unclear how sex may affect the initiation and maintenance of cannabis use in humans, animal studies strongly suggest that endogenous sex hormones modulate cannabinoid sensitivity. In addition, synthetic anabolic-androgenic steroids alter substance use and further support the importance of sex steroids in controlling drug sensitivity. The recent discovery that pregnenolone, the precursor of all steroid hormones, controls cannabinoid receptor activation corroborates the link between steroid hormones and the endocannabinoid system. This article reviews the literature regarding the influence of endogenous and synthetic steroid hormones on the endocannabinoid system and cannabinoid action.